2013
DOI: 10.1080/00405000.2013.826419
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysiological comfort characteristics of plated knitted fabrics

Abstract: Thermophysiological comfort properties of polyester elastane-plated fabric have been studied by varying the polyester filament shape factor, elastane linear density, and fabric loop length. Thermal and evaporative resistances were measured using sweating guarded hot plate. Absorption and wicking properties were measured using M/K GATS. Moisture management properties were measured by moisture management tester. Multilinear regression equations were calculated for all the properties by using generalized linear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Knitted fabrics have a good stretch property which offer better conformability and avoid excessive pressure between the garment and body [2]. Thermal comfort property of the textile fabric mainly depends on the heat and moisture transmission through the fabric [3]. Heat can be transferred by conduction from the solid fibres and entrapped air between the fibres, convection and radiation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Knitted fabrics have a good stretch property which offer better conformability and avoid excessive pressure between the garment and body [2]. Thermal comfort property of the textile fabric mainly depends on the heat and moisture transmission through the fabric [3]. Heat can be transferred by conduction from the solid fibres and entrapped air between the fibres, convection and radiation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to use surface resistance test principle, the MMT system can be suitable for the hydraulic conductivity characterization of small-capacity conductive sweat in the fabric surface, and used for unidirectional perspire measurement in sportswear [9]. However, the interaction between textile and liquid requires representation not only of limited liquid system, but more research and characterization of relatively unlimited liquid systems, especially for the thermal comfort of textile [10].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting polymer is then extruded through a spinneret by melt spinning. Manshahia and Das [178] investigated the thermophysiological comfort properties of knitted fabrics made of polyester staple fiber yarns and elastane monofilaments. The results showed that the air permeability and moisture-vapor permeability index of the fabrics were negatively influenced by the increase in linear density of the elastane filaments, possibly due to the associated increase in fabric tightness and density.…”
Section: Fiber Selection and Engineeringmentioning
confidence: 99%